Financial Feasibility and Prospects of Commercial Acid Lime Farming in Nepal - Subedi, Sanjiv; Timsina, Krishna Prasad (International Journal of Social Sciences and Management, 2023)
Research was conducted to assess the economics of commercial acid lime production and prospects of lime farming in Nepal. Morang, Sunsari, Chitwan and Nawalparasi districts of Nepal were selected as the study area after having consultation with concerned agricultural personnel. Altogether 70 farmers (19% of the sampling population) were randomly selected from the sampling frame to collect the primary information. The financial analysis of acid lime farming per hectare of land estimated NPV (12% discount rate) NRs. 4828734/ha, BCR 2.2, IRR 40% and the Pay-back period of 5 years, 5 months and 26 days. The BCR greater than one, IRR three times higher than discount rate, high NPV (return on investment more than cent percent) and payback period less than one-third of the total productive age of the lime orchard showed the financial feasibility of commercial acid lime farming in Nepal. The regression revealed that the import, production and productive area were found to be increased at the rate of 32, 6, and 8 percent per annum respectively while that of productivity was found to be decreased by 2.4 percent per annum (p< 0.010). There is a huge opportunity for acid lime farming in Nepal as the demand is much higher than the domestic production resulting voluminous import. Agribusiness promotion strategies focusing on market development should be introduced that would contribute to enhance the national acid lime production and promote the domestic market. Int. J. Soc. Sc. Manage. Vol. 10, Issue-1: 10-15.